2018
DOI: 10.1186/s12879-018-3507-9
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-associated bacterial flora in patients with benign prostatic hyperplasia: shift in antimicrobial susceptibility pattern

Abstract: BackgroundMen with urinary retention secondary to benign prostatic hyperplasia (BPH) are prone to genitourinary infections. Physicians should be aware of the current antimicrobial susceptibility pattern in this population if empirical treatment is needed. The goal of this study was to evaluate variations in prevalence, composition and antimicrobial susceptibility of bacterial flora in men with indwelling catheters subjected to surgery for BPH in chosen time periods since 1994. Necessary changes in empirical th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
(29 reference statements)
2
8
0
3
Order By: Relevance
“…27 Number of strains resistant to amikacin is convergent with data from Polish hospitals where around 10% of tested strains were resistant to amikacin. 30 , 31 Of note, in our study 33% of strains were characterized by resistance to ciprofloxacin. Similar rate (39.6% of resistant strains) was reported by Liou et al and these authors postulated the need for continued surveillance of antimicrobial resistance of Serratia spp.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…27 Number of strains resistant to amikacin is convergent with data from Polish hospitals where around 10% of tested strains were resistant to amikacin. 30 , 31 Of note, in our study 33% of strains were characterized by resistance to ciprofloxacin. Similar rate (39.6% of resistant strains) was reported by Liou et al and these authors postulated the need for continued surveillance of antimicrobial resistance of Serratia spp.…”
Section: Discussionsupporting
confidence: 45%
“…27 Number of strains resistant to amikacin is convergent with data from Polish hospitals where around 10% of tested strains were resistant to amikacin. 30,31 Of note, in our study 33% of strains were characterized by resistance to ciprofloxacin. Similar rate…”
Section: Discussionmentioning
confidence: 47%
“…Studies have shown that bacteria entering the urinary tract can be colonized by bacteria in distant organs through catheters and indicate the formation of biofilms in the mucous membranes of the organs, such as the prostate (40,41). Although studies have shown that the most common microorganism of catheter-related infection is Escherichia coli, it is often found that some drug-resistant bacteria can also enter the genitourinary tract through the catheter (42). Therefore, it is not surprising that bacteria in biofilms tend to be highly resistant to antibiotics and host immune defense mechanisms.…”
Section: Figure 1 |mentioning
confidence: 99%
“…microbial imbalance is closely associated with the initiation and development of prostate diseases, such as prostate cancer (PCa) and benign prostatic hyperplasia (BPH) ( 1,2). Imbalanced flora structures contribute to metabolic disruption in urinary system and immune response, resulting in carcinogenesis (3).…”
Section: Introductionmentioning
confidence: 99%